1998
DOI: 10.1379/1466-1268(1998)003<0168:fciara>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry is a rapid and reliable method for evaluating heat shock protein 70 expression in human monocytes

Abstract: The increasing interest in stress/heat shock proteins (Hsps) as markers of exposure to environmental stress or disease requires an easily applicable method for Hsp determination in peripheral blood cells. Of these cells, monocytes preferentially express Hsps upon stress. An appropriate fixation/permeabilization procedure was developed, combined with immunofluorescence staining and flow cytometry for the detection of the inducible, cytosolic, 72 kDa Hsp (Hsp70) in human monocytes. Higher relative fluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 0 publications
4
31
0
Order By: Relevance
“…Flow cytometry was used for the detection of Hsp70 and Hsp27 in lymphocytes (Xiao et al 2003;Bachelet et al 1998). Each fixed lymphocyte sample was divided into two to detect Hsp70 and Hsp27 separately as follows.…”
Section: Detection Of Hsp70 and Hsp27 Levels In Lymphocytesmentioning
confidence: 99%
“…Flow cytometry was used for the detection of Hsp70 and Hsp27 in lymphocytes (Xiao et al 2003;Bachelet et al 1998). Each fixed lymphocyte sample was divided into two to detect Hsp70 and Hsp27 separately as follows.…”
Section: Detection Of Hsp70 and Hsp27 Levels In Lymphocytesmentioning
confidence: 99%
“…Earlier studies that addressed compound induced manipulation of the heat shock response also measured Hsp70 expression (Yan et al 2004;Brundel et al 2006;Kato et al 1998), enabling easy comparison of previously identified compounds with new ones. First, we addressed whether flow cytometry could be used to study stress induced Hsp70 in several mouse cell types in a simple and rapid manner (Bachelet et al 1998). We analyzed Hsp70 expression in RAW264.7 macrophages, m-IC c12 intestinal crypt cells, primary bone marrow-derived dendritic cells (BMDC) and spleen cells.…”
Section: Analysis Of Hsp70 Expression By Flow Cytometrymentioning
confidence: 99%
“…1, B and C). Flow cytometric analysis of intracellular HSPs is a rapid, sensitive, quantitative, and more-reproducible method than Western blotting and is particularly suited for determining protein levels in individual cells (50,51). Moreover, heat-treated tumor cells displayed a characteristic phenotype with higher levels of TAAs (CEA and MUC1) and HLA-ABC (HLA-A2 and/or A24) (Fig.…”
Section: Characteristic Phenotype Of Ok/hs-fcsmentioning
confidence: 99%